Development and modeling of a colonoscopy robot - Tutcu, Cem. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2020., 2020)
Colorectal cancer is the second leading mortality cause among all cancer types. Similar to the other cancer types, early detection plays a vital role in the prevention of mortality. Colonoscopy is an endoscopic method that is widely used to screen colon, and remove legions, which is considered to be the most reliable method for detecting colorectal cancer. Conventional colonoscopes are propelled and positioned manually. This operation presents the risk of colon perforation, and patient discomfort due to high reaction forces applied to the colon wall. The conventional approach also often emerges the problem of colonoscope shaft looping inside the convoluted colon that causes loss of haptic feedback from the tip. Due to these post-colonoscopy complications, scans are not performed as frequently as required to mitigate the risks. In this study, a novel robotic solution is proposed for colonoscopy operations that will reduce operational risk, and improve patient comfort which will have an impact to increase colonoscopy scan rate. The robotic system also aims to provide a more ergonomic working environment for the colonoscopist to reduce long term usage complications. This thesis focuses on the colonoscopy robot development; particularly the design of an in-vivo shaft, kinematics and quasi-static modeling of the robot, and a medical application scenario. An experimental study is performed to prove navigation and position control capabilities of the system using a large scale prototype. Experiments showed that wall reaction forces are considerably lower than the conventional colonoscopy. Positioning tests have demonstrated close correlation with a model estimate up to a certain robot body length. This thesis proves the concept of a growing soft robot that can be further developed to be used in colonoscopy in future studies.
Keywords: Colonoscopy.